Eastern Han (AD 25-220) tombs in Sichuan - Chen, Xuan 1985- (Archaeopress Publishing Ltd, 2015)
This work explores the many factors underlying the extended popularity of the cliff tomb, a local burial form in the Sichuan Basin in China during the Eastern Han dynasty (AD 25-220). The development of the cliff tomb was linked to a complex set of connections involved with burial forms, and continued through associations with many other contemporary burial practices: brick chamber tombs, stone chamber tombs, and princely rock-cut tombs. These connections and links formed to a large extent through the incorporation of the Sichuan region within the Empire, which began in the fourth century BC.
Includes bibliographical references
Keywords: Tombs / China / Sichuan Sheng / History / To 1500; Burial / China / History / To 1500; Excavations (Archaeology) / China / Sichuan Sheng; Östliche Handynastie; Ausgrabung; Grab; Sichuan Sheng (China) / Antiquities; China / History / Han dynasty, 202 B.C.-220 A.D.; Sichuan